(untitled) (Biological Sciences - PJSIR, 2006)
Transient response characteristics of laboratory-scale spray columns and packed columns were studied by using impulse input tests. Using the results of impulse inputs, the dimensionless E-curves (normalized E-curves) were con- structed and the variance (s 2) of the exit age distribution function (E), and the dispersion number (D/uL), of the columns were computed using the dispersion model. This approach was useful for expressing the extent of mixing quantitatively, as well as evaluation of their comparative performance. It has been found that the dimensionless E-curves of the columns lie between plug flow and perfect mixing and the mixing pattern, whereas the extent of mixing in both spray and packed columns was found to be independent of the lengths of the columns. Nevertheless, the extent of mixing in the packed columns was much greater than in the spray columns.